#### Answer

=$-\frac{31}{45}$

#### Work Step by Step

$\frac{2}{7}(-\frac{14}{5})-(\frac{4}{3}-\frac{13}{9})\longrightarrow$ To evaluate expression in parentheses, first convert to least common denominator of 9.
=$\frac{2}{7}(-\frac{14}{5})-(\frac{4\times3}{3\times3}-\frac{13}{9})$
=$\frac{2}{7}(-\frac{14}{5})-(\frac{12}{9}-\frac{13}{9})$
=$\frac{2}{7}(-\frac{14}{5})-(-\frac{1}{9})\longrightarrow$ Evaluate multiplication.
=$-(\frac{28}{35})-(-\frac{1}{9})\longrightarrow$ Reduce using greatest common factor, 7.
=$-(\frac{28\div7}{35\div7})-(-\frac{1}{9})\longrightarrow$ Simplify.
=$-(\frac{4}{5})-(-\frac{1}{9})\longrightarrow$ Change subtraction of a negative to the additive inverse.
=$-(\frac{4}{5})+(\frac{1}{9})\longrightarrow$ To evaluate the addition, first convert to least common denominator of 45.
=$-(\frac{4\times9}{5\times9})+(\frac{1\times5}{9\times5})\longrightarrow$ Simplify.
=$-(\frac{36}{45})+(\frac{5}{45})\longrightarrow$ Add.
=$-\frac{31}{45}$